Potencial toxicológico do cádmio em dose semelhante à de exposição ocupacional na gênese de complicações no trato reprodutivo de ratas wistar - Costa, Charles Santos da (2023)
Cadmium (Cd) is a toxic heavy metal known to be a major endocrine disruptor. However, few studies have explored the effects of Cd exposure on developing polycystic ovary syndrome (PCOS) features and premature ovarian failure (POF). In this study, we evaluated whether subacute exposure to Cd at a dose similar to that of occupational exposure results in damage to the hypothalamic-pituitarygonadal (HPG) axis and abnormalities related to PCOS and FOP. Wistar rats were exposed to CdCl₂ (100 ppm in water for 30 days), we evaluated the levels of Cd in the blood, HPG axis and uterus. In addition, we evaluated metabolic factors, HPG axis function, reproductive tract morphophysiology, inflammation, oxidative stress and fibrosis. Exposure to Cd raised its levels in serum, HPG axis and uterus. The Cd rats presented metabolic damage, adiposity reduction, dyslipidemia and insulin resistance (IR). Cd also caused the HPG axis to malfunction. Irregularities in the estrous cycle, abnormal hypothalamic mRNA expression with overexpression of Kisspeptin 1 (Kiss1), androgen receptor (AR) and rapamycin mechanistic target protein (mTOR) and lower expression of Kiss1 (Kiss1R) and leptin receptors (LepR) were observed and tumor necrosis factor alpha (TNF-a), high levels of luteinizing hormone (LH), low levels of anti-Müllerian hormone (AMH) and abnormal ovarian follicular development, reduced ovarian reserve and follicle number antral were observed, suggesting ovarian depletion. Furthermore, exposure to Cd decreases the granulosa layer thickness and the corpora lutea counting and increases the cystic and atretic follicles. Cd exposure increased inflammation, oxidative stress, and remodeling in the reproductive tract. Finally, positive correlations were observed between serum and reproductive tract Cd levels with insulin resistance, dyslipidemia and estrous cycle duration, cystic and atretic follicles, LH levels and inflammation. Thus, these data suggest that subacute exposure to Cd at a dose similar to that of occupational exposure alters the function of the HPG axis, leading to PCOS and FOP features besides metabolic abnormalities in female rats.